ANALYSIS OF PROLANIS POLICY IMPLEMENTATION DURING THE COVID-19 PANDEMIC IN 2021 - Firdaus, D.Fitria Sari; Nadjib, Mardiati (UI Scholars Hub, 2022)
Data from Basic Health Research (Riskesdas) in 2018 shows that Diabetes and Hypertension dominate chronic diseases. The Director of BPJS Kesehatan has issued Circular No. 14 of 2020 concerning health services for national health insurance participants during the COVID-19 prevention period, especially Prolanis. The policy contains an appeal to postpone the provision of services in the form of mass gathering activities such as Prolanis Gymnastics, Club Education, and and other activities. Hence, this research is needed to describe the implementation of Prolanis policies during the COVID-19 Pandemic. The study used a descriptive research design with qualitative methods and George C. Edward III's theory of policy implementation model. The number of informants is 11 people. The data collection is done using observation, in-depth interviews, and document review. The study was conducted in May-June 2022 at the Krui Health Center, Pesisir Barat Regency, Lampung Province. The findings show that Prolanis activities, which were stopped during the COVID-19 Pandemic, resulted in uncontrolled hypertension and diabetes in the participants. There are also many Prolanis implementing officers and supervisors who are not aware of Circular 14 of 2020. This transmission failure resulted in implementing the policy not fully running correctly.